(untitled) (Law and world, 2021)
The role of mediation as mechanism for the amicable settlement of disputes is growing in the modern legal sector. Mediation is an alternative dispute resolution mechanism in modern law, and the Committee of Ministers of the Council of Europe recommended to use it in administrative disputes in 2001*. Mediation as the alternative dispute resolution mechanism is actively applied in civil disputes in Georgian legal sector, although it has not gained popularity in administrative disputes. Overwhelmed courts with administrative disputes and delayed justice once again underscores the need for reform, which may consider development of a new program to establish new mechanisms in administrative disputes and popularize application of new mechanisms. The use of mediation as an alternative dispute resolution mechanism in administrative-legal proceedings may have prospects, given its growing popularity in civil disputes and the methodology for resolving disputes amicably, although this requires judicial/legislative readiness. The goal of the study is to consider the perspective and possibility of using mediation in administrative disputes in order to demonstrate the need to use mediation as a mechanism.